Safety as A Component Element of The Quality of Tourist Services Provided - Susanna S. Alieva, (Researchparks Publishing, 2023)
The paper is devoted to the quality of a tourist product in terms of improving the safety of its receipt by a tourist. A detailed description of the above-mentioned component, which affects the quality of the tourist product, is given. At the same time, special attention, according to the authors, should be paid to financial guarantees for both local and international tourism, which should be aimed at meeting the needs for a quality tourism product.